The Influence of Green Awareness, Environmental Knowledge, Attitudes, And Subjective Norms, On The Purchase Intention Of Tote Bags As Environmentally Friendly Products - Puspitasari, Astika; Sekarsari, Larasati Ayu (At-Tadbir : jurnal ilmiah manajemen, 2024)
This study examines the relationship between environmental knowledge, product awareness, attitudes, subjective norms on consumer purchase intentions for tote bags as environmentally friendly products in Surabaya. The type of research used is quantitative research through a consumer survey approach. The sampling technique used was purposive sampling. Data collection is done by survey method through google form filled in by respondents. The research sample used was 150 respondents who had bought and used tote bag products in the Surabaya area. In this study, the test used in statistical analysis is hypothesis testing with PLS-SEM (Partial Least Square Structural Equation Modeling) software and WarpPLS 7.0. Based on the management results, (1) Environmental knowledge has a significant effect on Purchase Intention; (2) Product Awareness has a significant effect on Purchase Intention; (3) Attitude has a significant effect on Purchase Intention; and (4) Subjective Norms have no significant effect on Purchase Intention.